2018
DOI: 10.1097/lgt.0000000000000362
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Therapy for Vulvar Lichen Sclerosus—A Systematic Review

Abstract: According to the findings of our study, PDT seems to be promising in the treatment of patients with vulvar LS. Nonetheless, current knowledge is extremely limited, and further observational studies with large patient series are needed in the field to elucidate the efficacy of PDT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 23 publications
1
8
0
3
Order By: Relevance
“…PDT led to significant improvement in symptoms related to LS, but changes in histopathologic inflammation were inconsistent. 69 Although PDT seems promising, additional research is needed to determine efficacy of this treatment modality.…”
Section: Photodynamic Therapymentioning
confidence: 99%
“…PDT led to significant improvement in symptoms related to LS, but changes in histopathologic inflammation were inconsistent. 69 Although PDT seems promising, additional research is needed to determine efficacy of this treatment modality.…”
Section: Photodynamic Therapymentioning
confidence: 99%
“…It has a bimodal age distribution; its incidence peaks at prepubertal and postmenopausal ages. Even though several environmental and genetic factors were accused, it is believed that autoimmunity and chronic inflammation play essential roles in its pathogenesis [8][9][10]. Karadag et al [11] investigated 350 LS patients, 98% of which had vulvar involvement, and reported that autoimmune antibodies (anti-thyroid, anti-nuclear, anti-mitochondrial antibodies) were detected in 22%.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term treatment with these agents does not lead to regional atrophy, which is their main advantage over corticosteroids [2]. Other treatment options are oral acitretin, cyclosporin, methotrexate, topical progesterone, testosterone, ultraviolet A1 phototherapy, and photodynamic therapy [1,[8][9]. However, in complicated VLS which presents with structural deformities, severe adhesions, and scar formation, surgical treatment is indicated [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiologic rationale of photodynamic therapy (PDT) is based on the conversion of ALA and methyl δ-ALA into the photosensitizing metabolic products called protoporphyrins. By activating protoporphyrins with the appropriate wavelength, PDT induces production of ROS, like superoxide, and singlet oxygen [198]. These reactions ultimately result in apoptosis of lymphocytes and keratinocytes, as well as in alteration of the expression of both cytokines and MMPs, which play a role in skin remodelling.…”
Section: Photodynamic Therapymentioning
confidence: 99%